TRANSFORMASI LEKSIKON PERALATAN MASAK TRADISIONAL MASYARAKAT PULAU LEASE: KAJIAN ETNOLINGUISTIK DAN POTENSI PENGEMBANGAN AGRIBISNIS BERBASIS KEARIFAN LOKAL - Sulistiawati Aipassa; Yakobus C.W.Siubelan (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study aims to describe the transformation of the lexicon of traditional cooking utensils used by the Lease Island community and to examine the worldview and potential development of local wisdom–based agribusiness embedded in these lexicons. Employing an ethnolinguistic approach integrated with an agribusiness perspective, this research explores the interrelationship between language preservation, cultural values, and local economic empowerment. The data, consisting of lexicons of traditional cooking utensils, were collected through library research, field observations, and in-depth interviews conducted in three customary villages on Lease Island, namely Tuhaha, Ihamahu, and Ouw. The data were analyzed by classifying the lexicons according to their functions, linguistic forms, and cultural as well as economic meanings. The findings reveal that technological transformation has led to the decline in the use of traditional cooking utensil lexicons such as sempe, porna, tungku, balanga, tajela, aniong, and kamboti, which formerly embodied values of hard work, togetherness, honesty, and independence within the Lease Island community. From an agribusiness perspective, these lexicons and utensils represent a local agribusiness value chain encompassing raw material supply, production, processing, and distribution of traditional foods. The preservation of traditional lexicons thus functions not only as an effort to maintain cultural identity but also as a strategic resource for creative economic development, local culinary branding, and sustainable, culture-based agribusiness. This study underscores that the conservation of traditional lexicons is essential to sustaining linguistic, cultural, and economic continuity in the midst of modernization..